Antibody response in Hamsters Immunized against experimental Leishmaniasis (Baghdad Science Journal, 2011)
Direct agglutination test was used to evaluate the immunogenicity of three different antigens inoculated in hamsters as one , two and three doses which were: Group (1) inoculated with autoclaved killed Leishmania tropica , Group (2) inoculated with BCG vaccine alone while Group (3) inoculated with mixed antigens (autoclaved killed Leishmania "AKL"+ BCG).(4) Control animals inoculated with phosphate buffer saline.The maximum level of antibody titers were evaluated in animal inoculated with one , two or three dose of mixed antigens (320 , 640 and 1280) respectively when it compared with animals inoculated with corresponding doses of AKL antigen (80 , 160 and 320) respectively. While the minimum level of antibody titers were observed in animal inoculated with two and three dose of BCG (20 and 40) respectively.Our findings suggest that administration of BCG with AKL could lead to a potentially associated antibody response in animals, as well as, such response may evaluate the immunogenicity of some antigens.